2017
DOI: 10.1177/000313481708300839
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility and Cost of Postoperative Mammography Completed within One Year of Breast Conserving Therapy: Is it Worth It?

Abstract: Breast conserving therapy (BCT), lumpectomy followed by radiotherapy, is an effective treatment for a majority of breast cancers. According to the National Comprehensive Cancer Network, mammographic imaging should be completed at least six months after completion of radiation. This study evaluates the clinical significance and financial cost of postoperative breast imaging within one year of BCT. Patients treated with BCT between 2014 and 2016 at an academic center were identified retrospectively. The medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Included articles were published between 2017 and 2023, with data collection spanning 2012–2020. Studies in the US ( n = 19; 36%) [ 19 37 ] and Canada ( n = 9; 17%) [ 38 46 ] made up the majority of our identified studies ( n = 28; 53%), followed collectively by the Western European countries ( n = 22; 42%). In Western Europe, most studies were in Italy ( n = 5; 9%) [ 47 – 51 ], then Spain ( n = 4; 8%) [ 52 55 ], France ( n = 4; 8%) [ 56 59 ], Netherlands ( n = 3; 6%) [ 60 62 ], UK ( n = 3; 6%) [ 63 65 ], Sweden ( n = 2; 4%) [ 66 , 67 ], and Germany ( n = 1; 2%) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included articles were published between 2017 and 2023, with data collection spanning 2012–2020. Studies in the US ( n = 19; 36%) [ 19 37 ] and Canada ( n = 9; 17%) [ 38 46 ] made up the majority of our identified studies ( n = 28; 53%), followed collectively by the Western European countries ( n = 22; 42%). In Western Europe, most studies were in Italy ( n = 5; 9%) [ 47 – 51 ], then Spain ( n = 4; 8%) [ 52 55 ], France ( n = 4; 8%) [ 56 59 ], Netherlands ( n = 3; 6%) [ 60 62 ], UK ( n = 3; 6%) [ 63 65 ], Sweden ( n = 2; 4%) [ 66 , 67 ], and Germany ( n = 1; 2%) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of our 53 included studies, 15 (28%) reported person-level procedure costs [ 20 , 27 , 28 , 32 , 34 , 35 , 46 , 47 , 49 , 51 , 60 , 63 , 64 , 69 , 71 ]; 19 (36%) reported person-level costs over a 1-year time horizon [ 19 , 23 , 25 , 26 , 29 , 33 , 38 40 , 43 , 45 , 48 , 50 , 52 , 56 59 , 65 ]. As such, the costs from 34 (64%) studies per person for procedures and then over a 1-year time frame are presented in Table 3 and 4 , respectively, with the other included studies’ costs presented in Supplementary Excel Sheet 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Con respecto a la periodicidad, aunque hay evidencia de estudios retrospectivos que sugiere que el seguimiento semestral permite una mayor identificación de recurrencias tempranas (46), esto no parece generar ningún beneficio clínico adicional (47). Sobre el inicio del seguimiento después de la cirugía conservadora, la mayoría de la literatura apunta a la ausencia de un beneficio claro con la mamografía tomada antes del año (48,49). En principio, no debería solicitarse la mamografía antes de los seis primeros meses tras la finalización de la radioterapia (21,41,49,50).…”
Section: Imágenes Mamariasunclassified
“…Worldwide, breast cancer is the most common malignancy in women and the leading cause of cancer-related death in women [1,2]. However, early detection with screening mammograms and recent advances in cancer therapy have led to a decrease in breast cancer mortality [2,3]. The surgical management of breast cancer has evolved from radical mastectomy to breast conserving surgery followed by adjuvant radiation therapy [i.e., breast conserving therapy (BCT)], which achieves equivalent disease outcomes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%